2000
DOI: 10.1128/aac.44.12.3351-3356.2000
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Spectrum of a Novel Des-Fluoro(6) Quinolone, BMS-284756

Abstract: The in vitro spectrum of a novel des-fluoro(6) quinolone, BMS-284756, was compared with those of five fluoroquinolones (trovafloxacin, moxifloxacin, levofloxacin, ofloxacin, and ciprofloxacin). BMS-284756 was among the most active and often was the most active quinolone against staphylococci (including methicillin-resistant strains), streptococci, pneumococci (including ciprofloxacin-nonsusceptible and penicillin-resistant strains), and Enterococcus faecalis. BMS-284756 inhibited Ϸ60 to Ϸ70% of the Enterococcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
118
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(126 citation statements)
references
References 6 publications
6
118
1
1
Order By: Relevance
“…Three isolates tested in both studies had the same susceptibilities in both studies. Three other studies reported on the garenoxacin MICs for small numbers of C. pneumoniae isolates (8,9,27). The methods used in those studies either differed from those used in our study or were not reported, and therefore, a comparison of the results must be made with caution because of possible methodological differences (11,24).…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…Three isolates tested in both studies had the same susceptibilities in both studies. Three other studies reported on the garenoxacin MICs for small numbers of C. pneumoniae isolates (8,9,27). The methods used in those studies either differed from those used in our study or were not reported, and therefore, a comparison of the results must be made with caution because of possible methodological differences (11,24).…”
Section: Discussioncontrasting
confidence: 40%
“…The methods used in those studies either differed from those used in our study or were not reported, and therefore, a comparison of the results must be made with caution because of possible methodological differences (11,24). However, all garenoxacin MICs reported have ranged from Ͻ0.008 to 0.015 g/ml, and MBCs were equal to the MIC or were 1 twofold dilution higher, while the levofloxacin and moxifloxacin MICs were higher, usually 2 to 5 twofold dilutions for MIC testing (8,9,27).…”
Section: Discussionmentioning
confidence: 50%
“…It has been shown to have activity against a wide range of clinical isolates (1,7,12,34), and in particular, garenoxacin has been shown to have good activity against Staphylococcus aureus, both methicillin sensitive and resistant (6), and the respiratory pathogens Streptococcus pneumoniae (26), Haemophilus influenzae, and Moraxella catarrhalis (8). The activity of garenoxacin has been further assessed against strains of S. aureus with specific topoisomerase mutations (21), and more recently, it has been shown that garenoxacin has similar potency against both topoisomerase IV and gyrase (16) (dual-targeting quinolone), thus requiring mutations in both topoisomerases for resistance to occur (29).…”
mentioning
confidence: 99%
“…Moraxella catarrhalis is of particular importance as a cause of CAP in patients with chronic bronchitis. 4,5 Since, organisms express themselves in a stereotypical fashion, an etiologic classification of pneumonia correlates with the patient's signs and symptoms. Elderly patients will often have only the infiltrate, which is not always accompanied by fever or leukocytosis.…”
Section: Discussionmentioning
confidence: 99%